Tales from a not-so-graceful ice princess - Russell, Rachel Renee (New York : Aladdin, 2012)
When her crush Brandon reveals that the animal shelter where he volunteers is in danger of being closed, Nikki and her friends enter an ice skating competition to help raise money, an effort that is compromised by an interfering Mackenzie.
4.9
3-6
750
W
Keywords: Skating -- Juvenile fiction; Contests -- Juvenile fiction; Money-making projects for children -- Juvenile fiction; Animal shelters -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Popularity -- Juvenile fiction; Ice skating -- Fiction; Contests -- Fiction; Moneymaking projects -- Fiction; Animal shelters -- Fiction; Popularity -- Fiction; Middle schools -- Fiction; Diaries -- Fiction; Schools -- Fiction; School stories; Humorous stories; Friendship -- Fiction; Diary fiction